'Dégage RCD!' The rise of internal dissent in Ben Ali's Constitutional Democratic Rally and the Tunisian uprisings. Issue 2 (3rd April 2018) - Wolf, Anne
Abstract: This article examines the historical evolution of Tunisia's Constitutional Democratic Rally (RCD) from its beginnings in 1987, when President Zine el-Abidine Ben Ali took power, until his ousting in 2011 when the party was outlawed. I argue that the RCD evolved from a political force with wide popular support during a short democratic era (1987–89) into a repressive interest group in the 1990s, when the regime cracked down on political dissidents and popular freedoms whilst rewarding party members with lucrative benefits. In the 2000s the RCD adopted a quasi-mafiosi structure that profited the Ben Ali family, which increasingly monopolized economic and political power. Tunisia's transformation into a near dynasty marginalized many RCD members and its wider networks, a central dynamic to understand Ben Ali's ousting in 2011.